A Nexus Between Liquidity & Profitability: A Study Of Trading Companies In Sri Lanka. - Ajanthan, A. (My University, 2013)
This study has investigated the relationship between liquidity and profitability of trading companies in Sri Lanka. The main objective was to examine the nature and extent of the nexus between liquidity and profitability in profit-oriented quoted trading companies and also to determine whether any relationship exist between the two performance measures. Analysis was based on data extracted from annual reports and accounts of the companies for the relevant period. Correlation and regression analysis respectively were employed to examine the nature and extent of the relationship between the variables and determine whether any cause and effect relationship between them. The study covered 08 listed trading companies in Sri Lanka over a period of past 5 years from 2008 to 2012. Correlation& regression analysis and descriptive statistics were used in the analysis and findings suggest that there is a significant relationship exists between liquidity and profitability among the listed trading companies in Sri Lanka. However, the findings of this paper are based on a study conducted on the selected companies. Hence, the results are not generalizable to non-quoted companies. Secondly, the sample only comprises trading companies. Therefore, the results are valid for this sector.
Keywords: Liquidity; Profitability; Trading companies